1998
DOI: 10.1002/(sici)1521-4141(199802)28:02<560::aid-immu560>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive expression of Bcl-xL or Bcl-2 prevents peptide antigen-induced T cell deletion but does not influence T cell homeostasis after a viral infection

Abstract: We examined the CD8+ T cell response to lymphocytic choriomeningitis virus (LCMV) in mice doubly transgenic for an LCMV-specific TCR and for either bcl-xL or bcl-2. Clonal down-sizing of the anti-viral CD8+ T cell response and the generation of T cell memory was not influenced by constitutive expression of these anti-apoptotic proteins in T cells. Expression of Bcl-xL or Bcl-2 did, however, prevent LCMV peptide-induced peripheral deletion of mature CD8+ T cells in vivo and apoptosis of activated LCMV-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 46 publications
5
42
1
Order By: Relevance
“…Taken together with the decrease extent of Bcl-2 clone 4 T cells apoptosis as compared with wild-type clone 4 T cells (Fig. 2C), these data suggest that the protective effects of Bcl-2 are due to a reduction in apoptosis of the activated cells, which is consistent with a role for a Bcl-2-sensitive mechanism in CD8 T cell tolerance (37).…”
Section: Cd8 T Cell Peripheral Tolerance Can Be Inhibited By Over-expsupporting
confidence: 93%
“…Taken together with the decrease extent of Bcl-2 clone 4 T cells apoptosis as compared with wild-type clone 4 T cells (Fig. 2C), these data suggest that the protective effects of Bcl-2 are due to a reduction in apoptosis of the activated cells, which is consistent with a role for a Bcl-2-sensitive mechanism in CD8 T cell tolerance (37).…”
Section: Cd8 T Cell Peripheral Tolerance Can Be Inhibited By Over-expsupporting
confidence: 93%
“…It is possible a low level still persisted, but we favor the notion that they may have eventually died. This result would correlate with previous data on CD8 cells obtained from Bcl-x L transgenic mice in which Bcl-x L antagonized apoptosis of effector cells, but only delayed the contraction phase of an Ag-induced CD8 T cell response rather than preventing it (32). Recent results have suggested that recruitment of host cells is essential to the therapeutic action of adoptively transferred CD8 cells, rather than these cells directly targeting the tumor (27,33).…”
Section: Discussionmentioning
confidence: 99%
“…3A). These results are consistent with previous reports demonstrating that in the absence of proinflammatory signals, activation of naive CD8 T cells with soluble peptide can lead to significant levels of deletion (9,13,17,18,25,26). Tolerance induction with 10, 1, and 0.1 g doses of HA peptide also led to comparable deletion of the naive clone 4 T cells (Fig.…”
Section: Deletion Vs Anergy Of Peptide Tolerized Clone 4 T Cells In Vivomentioning
confidence: 99%